Oral supplementations of Bauhinia variegata’s leaf extract has anxiolytic effect and improves locomotory and exploratory behavior of female albino mice - Furhan Iqbal; Muhammad Jahangir; Asmat Ullah; Muhammad Naseer Khan Khattak; Shahid Iqbal (International Journal of Phytomedicine, 2017)
Present study was designed to investigate the effects of 200 mg/ml solvent/Kg of body weight of Bauhinia variegata’s leaf extract on neuromuscular coordination, locomotory and exploratory behavior of adult female albino mice. Six week old female albino mice were used as experimental animals. Mice were either orally supplemented with 200 mg/ml/Kg of body weight Bauhinia variegata’s leaf extract or with saline solution [0.9%] for 7 days. Behavioral observations were made by applying a series of neurological tests [Rota rod, Elevated plus maze, Light and dark box, Open field and Novel object test]. Exploratory and locomotory behavior during Open Field test was improved in leaf extract treated mice as they had more means speed [P = 0.01], rotations [P = 0.001], clockwise rotations [P = 0.004] and anti-clockwise rotations [P = 0.001] than control mice. Bauhinia variegata’s leaf extract treated mice had higher transition frequency [P = 0.002] and spent more time in light compartment during light dark box test than saline treated controls. Bauhinia variegata’s leaf extract treated mice covered more distance [P = 0.033] with higher speed [P = 0.028] compared to control mice during Elevated Plus Maze test. Bauhinia variegata’s leaf extract improves the locomotory and exploratory behavior in adult female albino mice. Leaf extract of Bauhinia variegate can be further explored to be used as a therapeutic agent for the treatment of neurological ailments.